Observation of Si 2p Core‐Level Shift in Si/High‐κ Dielectric Interfaces Containing a Negative Charge - Lehtiö Juha-Pekka; Rad Zahra Jahanshah; Granroth Sari; Yasir Muhammad; Punkkinen Marko; Punkkinen Risto; Hedman Hannu-Pekka; Rueff Jean-Pascal; Rauha Ismo TS; Savin Hele; Laukkanen Pekka; Kokko Kalevi (WILEY, 2022)
Negative static charge and induced internal electric field have often been observed in the interfaces between silicon and high‐κ dielectrics, for example Al2O3 and HfO2. The electric field provides either beneficial (e.g., field‐effect passivation) or harmful (e.g., voltage instability) effect depending on the application. Different intrinsic and extrinsic defects in the dielectric film and interface have been suggested to cause the static charge but this issue is still unresolved. Here spectroscopic evidence is presented for a structural change in the interfaces where static charge is present. The observed correlation between the Si core‐level shift and static negative charge reveals the role of Si bonding environment modification in the SiO2 phase. The result is in good agreement with recent theoretical models, which relate the static charge formation to interfacial atomic transformations together with the resulting acceptor doping of SiO2.